RELICTS OF THE EARLIEST UNDERSTANDING OF FAIRNESS, JUSTICE AND LAW IN THE FIRST STATES OF ANTIQUITY – A LEGAL-ANTHROPOLOGICAL VIEW - Stanimirovic, Vojislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Abstract: All archaic societies were founded on the principles of equality and solidarity. Another common trait were the mechanisms for regulating social behavior, as they were crucial for a society’s survival. In such types of societies, archaic fairness existed. It manifested itself through egalitarianism, solidarity, but also through the static and conservative elements and was based on the customs which were binding on all the members of the society. When archaic societies became layered and started to expand and mix with other communities, the initial cohesion, security and archaic fairness slowly started to disappear and instead, the concept of justice appeared. Unfortunately, that caused an irreversible damage to the balance that once existed as the ideal state in the archaic societies.The invention of the writing system and the creation of the first states eventually enabled the Cuneiform Law to develop and as the result, the first law codes of the humanity came to life. The first states and their rulers found themselves at the crossroads between “the old” and “the new”. The law was heavily shaped by the nobility, so all of the privileges were created explicitly for the nobles, while the poor were yearning for the past times which were more kind to them. The new law slowly started to suppress the old customs. The ancient rulers, at least instinctively, if not consciously, recognized the need for a balance which would guarantee order and peace in the state. In Egypt, where the archaic elements survived the longest, the echoes of archaic societies and ancient beliefs could be found in the principle of Ma’at, the weighing of souls and the Book of the dead. The creators of Cuneiform Law also found their ways and strategies to present themselves as just and caring rulers. The evidence for that can be found especially in the provisions of the law. Whether they are referring to their own achievements and merits, or offering protection and care to the vulnerable members of the society, or revoking privileges of the nobles for the sake of the greater good, or turning back to the tradition, or “buddying up” with the gods, or determining measures and compensation amounts, they are, above all, trying to be exemplary rulers to their subjects by putting the rule of law first.
Keywords: Key words: Archaic societies. – Fairness. – Justice. –Law. – Cuneiform law codes.